2007
DOI: 10.1302/0301-620x.89b8.19134
|View full text |Cite
|
Sign up to set email alerts
|

The use of gravity or manual-stress radiographs in the assessment of supination-external rotation fractures of the ankle

Abstract: Supination-external rotation (SER) fractures of the ankle may present with a medial ligamentous injury that is not apparent on the initial radiographs. A cadaver gravity-stress view has been described, but the manual-stress view is considered to be the examination of choice for the diagnosis of medial injuries. We prospectively compared the efficacy of these two examinations. We undertook both examinations in 29 patients with SER fractures. Of these, 16 (55%) were stress-positive, i.e. and had widening of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 18 publications
(27 reference statements)
1
111
0
2
Order By: Relevance
“…There was no signiWcant diVerence between the gravity and the manual-stress radiograph with regard to mean medial clear space or talar shift measured in association with either fracture pattern [18]. The VAS score for examinations of manual-stress indicated that patients perceived more discomfort than with gravity testing [45]. The main limitation of the gravity-stress radiograph is the inability to control dorsiXexion and plantar Xexion [18].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…There was no signiWcant diVerence between the gravity and the manual-stress radiograph with regard to mean medial clear space or talar shift measured in association with either fracture pattern [18]. The VAS score for examinations of manual-stress indicated that patients perceived more discomfort than with gravity testing [45]. The main limitation of the gravity-stress radiograph is the inability to control dorsiXexion and plantar Xexion [18].…”
Section: Discussionmentioning
confidence: 93%
“…An overview is shown in Tables 1 and 2. Three trails investigated medial tenderness [12,16,29]; two studies, ecchymosis [16,29]; two studies, swelling [16,29]; one study, an injury radiograph [46]; six studies, a type of radiographic stress view [12,16,18,29,32,35,45]; one study, the Lauge-Hansen classiWcation [46]; one study, MRI [24]; and one article studied arthroscopy [46] in the evaluation of the deltoid ligament integrity. The publication dates span 6 years; in 2001, Michelson et al [32] was the earliest and in 2007, Koval et al [24] and Schock et al [45] were the most recent publications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With clinical findings of medial-sided tenderness, swelling or ecchymosis being unreliable in detecting deep deltoid incompetence, 3 there are advocates of proceeding to examination under anaesthesia (EUA), magnetic resonance imaging (MRI), 4 ankle arthroscopy 5 or stress radiographs. 6,7 The early accurate differentiation between a stable SER-II from an unstable SER-IV injury can potentially ease pressure on the already over-burdened fracture clinics and allow earlier return of function.…”
mentioning
confidence: 99%